Ninjin'yoeito Targets Distinct Ca2+ Channels to Activate Ghrelin-Responsive vs. Unresponsive NPY Neurons in the Arcuate Nucleus - Goswami, Chayon; Dezaki, Katsuya; Wang, Lei; Inui, Akio; Seino, Yutaka; Yada, Toshihiko (Frontiers in Nutrition, 2020)
Appetite loss or anorexia substantially deteriorates quality of life in various diseases, and stand upstream of frailty. The substance that counteracts appetite loss has long been awaited. Neuropeptide Y (NPY) in the hypothalamic arcuate nucleus (ARC) and ghrelin released from stomach are the most potent central and peripheral inducers of appetite, respectively. We previously reported that Ninjin’yoeito, a Japanese kampo medicine comprising twelve herbs, restores food intake and body weight in cisplatin-treated anorectic mice. Furthermore, Ninjin’yoeito increased cytosolic Ca2+ concentration ([Ca2+]i) in both ghrelin-responsive and unresponsive NPY neurons in ARC. However, significance of Ninjin’yoeito activation of two NPY neuron subpopulations remains unknown. This study sought to determine the occupancy of ghrelin-responsive vs. unresponsive NPY neurons in ARC and to explore the mechanisms underlying [Ca2+]i increases in these two NPY neuron subpopulations. Single neurons were isolated from ARC of mice, subjected to measurement of [Ca2+]i with fura-2, and subsequently immunostained for NPY. Among ARC NPY neurons, 58% responded but 42% did not respond to ghrelin with [Ca2+]i increases. In ghrelin-responsive ARC neurons, Ninjin’yoeito (10 µg/ml)-induced increases in [Ca2+]i were inhibited in Ca2+ free condition and by N-type Ca2+ channel blocker, -conotoxin, but not by L-type Ca2+ channel blocker, nitrendipine. In contrast, in ghrelin-unresponsive ARC neurons, Ninjin’yoeito-induced [Ca2+]i increases were inhibited in Ca2+-free condition and by nitrendipine but not -conotoxin. These results indicate that ghrelin-responsive and unresponsive NPY neurons are the major populations in ARC and activated by Ninjin’yoeito through distinct mechanisms, via N-type Ca2+ channels in ghrelin-responsive while L-type Ca2+ channels in ghrelin-unresponsive neurons. We suggest ARC N- and L-type Ca2+ channels as the potential targets for activating, respectively, ghrelin-responsive and unresponsive NPY neurons to treat anorexia.